Mekanisme Regenerasi Anggota Tubuh Hewan - Lukman, Aprizal (Universitas Jambi, 2009)
Morphogenetic process of ontogenetic cycle is the destruction model of certain systemthat had been developed in advanced. An animal organism occupy an ability to fix its own hurtextensively due to natural or physical accident on experiment.